Association Between HDL-C and Bone Mineral Density: An Cross-Sectional Analysis - Niu P (Dove Medical Press, 2021)
Peng Niu,1 Haibo Li,2 Dejun Liu,2 Yan Feng Zhang,1 YongXi Liu,1 Cheng Liang3 1Department of Spine and Joint Surgery, Second General Hospital of Nanyang, Nanyang City, 473009, Henan Province, People’s Republic of China; 2China Department of Orthopaedics, People’s Hospital of Xuecheng, Zaozhuang City, 277000, Shandong Province, People’s Republic of China; 3The Orthopaedic Center of Joint and Trauma Surgery, The Affiliated Hiser Hospital of Qingdao University, Qingdao City, Shandong Province, 266000, People’s Republic of ChinaCorrespondence: Cheng Liang Tel +86 15589897463Email 593441085@qq.comBackground: Dyslipidemia has been found to contribute to increased risk of osteoporosis and its association with bone mineral density (BMD) remains controversial. We determined whether blood lipid levels are linked with change of BMD.Methods: In a large sample from the MIDUS II study, we sought to evaluate the relationship between blood lipid levels and BMD. Multivariate linear regression models and smooth curve analysis were constructed by controlling a great range of confounding factors.Results: The median age of them was 52.5 years, and the number of males was 176 (40%). Univariate analysis showed that blood high-density lipoprotein-cholesterol (HDL-C) level was negatively related to lunar total femur (r = − 0.266, P < 0.001), lunar radius ultradistal (UD) (r = − 0.297, P < 0.001), lunar radius 1/3 (r = − 0.307, P = 0.001) and femoral neck (r = − 0.172, P = 0.001). In multivariate linear analysis, except for blood triglyceride, total cholesterol and low-density lipoprotein cholesterol (LDL-C), we found that blood HDL-C level was still negatively related to lunar total femur [B = − 0.002, B 95% CI (− 0.002, − 0.001), P < 0.001], lunar radius UD [B = − 0.001, 95% CI (− 0.001, 0), P = 0.002], lunar radius 1/3 [B = − 0.001, 95% CI (− 0.001, 0), P = 0.003] and femoral neck [B = − 0.001, 95% CI (− 0.002, 0), P = 0.039] after adjustments of demographic characteristics, lifestyle, disease history were made. Furthermore, we found that age, sex, and body mass index (BMI) had modifying effects on this negative association.Conclusion: This study confirmed the negative association between HDL-C and BMD in the observational analysis from (MIDUS) study and provides high-quality evidence that age, sex and BMI had modifying effects on this negative association.Keywords: blood lipid, bone mineral density, osteoporosis, MIDUS II study